2015
DOI: 10.17843/rpmesp.2015.324.1766
|View full text |Cite
|
Sign up to set email alerts
|

Oferta y composición nutricional de ensaladas en patios de comida de centros comerciales de Lima Metropolitana, 2014

Abstract: RESUMENObjetivos. Evaluar la oferta y composición nutricional de las ensaladas ofrecidas como plato principal en los patios de comida de los centros comerciales de Lima, Perú. Materiales y métodos. Se revisó las cartas de comida de todas las franquicias presentes en los patios de comida de los once centro comerciales de Lima, luego se evaluó la composición nutricional de las ensaladas ofertadas como plato principal calculando su contenido calórico, proteico, carbohidratos, grasas, colesterol, fibra y sodio, y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…This may be partially explained by the fact that vegetable intake in the present study was self-reported through a question that specifically inquired about vegetable salad consumption. Because many culinary differences exist in vegetable salad elaboration in Peru, which may even include starchy vegetables as the main ingredient (i.e., potatoes, sweet potatoes, corn) and high-caloric salad dressings [66], a significant association with vegetables may have been neglected.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…This may be partially explained by the fact that vegetable intake in the present study was self-reported through a question that specifically inquired about vegetable salad consumption. Because many culinary differences exist in vegetable salad elaboration in Peru, which may even include starchy vegetables as the main ingredient (i.e., potatoes, sweet potatoes, corn) and high-caloric salad dressings [66], a significant association with vegetables may have been neglected.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…In this sense, the assessment of environments for the promotion of healthy eating patterns is transcendent. In fact, a study carried out in food courts of shopping centers in Peru found that of all the food services available, only 25% offered the option of consuming vegetables in the form of a salad and that of all the menus available, only four, 7% offered this type of preparation [51]. Since fruits and vegetable intake is a distinctive element of healthy eating patterns, such as that of the Mediterranean, not having available options that promote a varied and balanced diet makes it difficult to achieve high levels of AMedD.…”
Section: Factors Associated With Ameddmentioning
confidence: 99%
“…La OMS plantea una serie de recomendaciones individuales y públicas para lograr una alimentación saludable y la regulación de las enfermedades crónicas, que incluyen el mantener un equilibrio energético, controlar el peso corporal en un nivel saludable, la modificación de la calidad de las grasas, el aumento en el consumo de frutas, verduras, leguminosas, cereales integrales y semillas oleaginosas, así como la reducción de alimentos que aportan carbohidratos de absorción rápida y sal (4) . Sin embargo, estas directrices han sido difíciles de ejecutar por diversas razones, entre ellas, la interpretación del concepto "alimentación saludable" que, en ocasiones, no responde a la idea esencial de esta definición (5) . Frente a esta situación, es necesario identificar alguna estrategia que permita de realizar y mantener adecuadamente una alimentación saludable.…”
Section: Introductionunclassified